A case of encephalomyeloradiculopathy in a non-carcinomatous patient associated with P/Q type voltage gated calcium channel antibodies. (November 2016) - Kaur, Divpreet; Raheja, Divisha
Highlights: Paraneoplastic antibodies should be checked in patients presenting with neurologic symptoms of undetermined etiology. Paraneoplastic antibodies should be checked in these patients despite a negative workup for occult malignancy. P/Q type voltage gated calcium channel (VGCC) antibodies can be seen beyond Lambert Eaton Syndrome. P/Q type VGCC antibodies can have multifocal involvement (central and peripheral). Abstract: The presence of P/Q type voltage gated calcium channel (VGCC) antibodies has been strongly correlated with Lambert Eaton Syndrome (LES), present in 90% of non-immunocompromised patients with LES. However, there have been case reports which have shown its association between paraneoplastic syndrome affecting both central nervous system and the peripheral nervous system causing encephalomyelitis and sensory neuronopathy/neuropathy. We present a case of a young man, who presented with encephalomyelitis, and was further noted to have superimposed cervical polyradiculopathy associated with P/Q type VGCC antibodies.